The adoption of generic drugs by a hospital: effects on drug dispensation among community pharmacies - Tomoya Tachi; Kosuke Saito; Hiroki Esaki; Ikuto Sugita; Aki Yoshida; Yuta Kanematsu; Yoshihiro Noguchi; Michi Umeda; Masahiro Yasuda; Takashi Mizui; Teruo Tsuchiya; Chitoshi Goto; et al. (BMC, 2018)
Abstract Background The objective of the current study is to elucidate the effect that the adoption of generic drugs by a large hospital has on the dispensation of generic drugs by community pharmacies. We evaluated the percentage of generic drugs dispensed by pharmacies and the cost of drugs dispensed before and after the adoption of generic drugs by a large hospital. Methods Participants comprised patients who were admitted to Gifu Municipal Hospital prior to its adoption of generic drugs (November 1, 2013 to November 14, 2013) and after its adoption (November 1, 2014 to November 14, 2014) and who utilized generic drugs dispensed by pharmacies. Results Results indicated that the pre-adoption dispensation rate of generic drugs by pharmacies was 48.3% (477/926 drugs), while the post-adoption rate was 57.7% (604/1046 drugs), indicating an increase of 9.4 points (P < 0.001). Furthermore, an investigation into the price paid for generic drugs as a percentage of the total price paid for all drugs indicated the following: the pre-adoption percentage was 23.5% (9756/41,461 yen), and the post-adoption percentage was 34.1% (19,221/56,438 yen), indicating an increase of 10.6 points (P < 0.001). Conclusions The results of this study revealed that the adoption of generic drugs by a hospital may promote the use of generic drugs by pharmacies and lead to reduced medical costs as well.